Clinical evidence and mechanistic pathways of human milk oligosaccharide supplementation for health benefits: an updated review - Amin, Tanjina; Amin, Md Mahmudul; Adikari, Adikari Arachchige Dilki Indrachapa; Zheng, Xiaoming; Ning, Yibing; Wang, Bing (Frontiers in Nutrition, 2025)
Human milk oligosaccharides (HMOs), a diverse group of complex sugars, are increasingly recognized for their health advantages for infants. These bioactive molecules are believed to be critical in shaping gut microbiota, infant immunity, and overall health. Recent clinical studies have focused on supplementation of infant formulas with manufactured HMOs to replicate some of the benefits observed in breastfed infants. This review aims to summarize the latest evidence from human clinical trials on manufactured HMO supplementation, highlighting its associated health benefits and the underlying mechanisms of action. A comprehensive literature search was conducted using PubMed, Medline, and Scopus databases from 1964 to 2024, identifying clinical intervention studies on manufactured HMOs across different populations, ranging from pre-term infants to adults with or without medical conditions. Findings reveal that manufactured HMOs are safe, well-tolerated, and show promising benefits for immune health and gut microbiota composition, closely mirroring the effects of natural HMOs found in breast milk. Although studies have explored the prebiotic role of HMOs in modulating neuroactive metabolites such as short-chain fatty acids (SCFAs) produced by gut microbiota, there is a notable lack of research directly evaluating the cognitive outcomes of HMOs using MRI or standardized developmental assessment tools. Furthermore, this review highlights two novel clinical findings: the potential therapeutic role of HMOs in obesity prevention by promoting fat loss while preserving muscle mass and their beneficial effects in osteoarthritis by reducing pain and enhancing mobility. However, the variability in dosage, participant groups, intervention duration, and outcomes, along with the limited studies on the mechanistic pathways of HMOs, makes it difficult to draw definitive conclusions, underscoring the need for well-designed clinical trials across diverse health conditions to better understand the full potential of HMO supplementation.